The Effect of Marketing Mix on Decisions to Purchase Oppo Brand Smartphones at Plaza Simpur Center in Bandar Lampung - Yustianto, Benny Prakarsa; Syarif , Arman (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine how the marketing mix influences consumers' decisions to purchase Oppo smartphones at Plaza Simpur Center in Bandar Lampung. Methodology: A proportional random sampling method was used to select 100 customer respondents. This study employs a quantitative methodology, involving the selection of a specific area for investigation and the collection of data through documents, interviews, and questionnaires. Results: The marketing mix has a significant impact on consumers' decisions to buy Oppo smartphones at Plaza Simpur Center in Bandar Lampung. Limitations: The study focuses solely on Oppo, a well-known smartphone brand, and does not examine the effects of increased marketing on other competing brands or in other shopping centers. Contribution: The study's findings provide valuable insights for marketers and marketing firms in developing effective marketing mix strategies for sales in Lampung province.